Sensory Disturbance by Six Insecticides in the Range of μg/L in Caenorhabditis elegans - Zhou, Rong; Yu, Yue; Zhang, Weidong; Wang, Dayong; Bai, Yanan; Wang, Yixuan; Bu, Yuanqing (Frontiers in Environmental Science, 2022)
Using Caenorhabditis elegans as an animal model, the possible toxic effects of six insecticides (dinotefuran, thiamethoxam, thiacloprid, nitenpyram, acetamiprid, and sulfoxaflor) commonly used in agriculture on sensory perception were examined. The sensory behaviors of thermotaxis, avoidance of copper ion, chemotaxis to NaCl, and chemotaxis to diacetyl were measured to investigate the damage on sensory perceptions in nematodes exposed to the examined insecticides in the range of micrograms per liter (μg/L). Exposure to dinotefuran, thiamethoxam, thiacloprid, nitenpyram, acetamiprid, or sulfoxaflor at concentrations of 10–100 μg/L resulted in severe deficits in sensory perceptions to temperature, copper ion, NaCl, and diacetyl. The relative neurotoxicity of the six insecticides examined to C. elegans were shown as dinotefuran > thiamethoxam > thiacloprid > nitenpyram > acetamiprid > sulfoxaflor. Moreover, post-treatment with the antioxidant ascorbate effectively suppressed the production of reactive oxygen species and damages of sensory perceptions induced by the six insecticides, indicating that the activation of oxidative stress can act as an important cellular contributor to the observed damage of the examined insecticides in affecting sensory perceptions. Our data highlighted the potential toxicity of the six insecticides at low concentrations in inducing sensory disturbance to environmental organisms.